1997
DOI: 10.1161/01.str.28.7.1386
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Visual Neglect on Stroke Rehabilitation

Abstract: Patients with visual neglect managed on a stroke unit have similar destination of discharge despite lower Barthel Index scores compared with patients of equal stroke severity who do not have this deficit. Spatiomotor cueing and early emphasis on function can improve outcome and reduce resource use in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
125
2
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(140 citation statements)
references
References 28 publications
7
125
2
6
Order By: Relevance
“…Visual scanning training alone was shown to improve significantly neglect in one level Ib study (Weinberg et al, 1977). Spatiomotor or visuo-spatiomotor cueing improved neglect significantly in one level Ib (Kalra et al, 1997) and two level IIa studies (Lin et al, 1996;Frassinetti et al, 2001). Visual cueing with kinetic stimuli was found to bring significant, albeit transient, improvement in three level IIa studies (Butter et al, 1990;Pizzamiglio et al, 1990;Butter and Kirsch, 1995).…”
Section: Rehabilitation Of Ulnmentioning
confidence: 93%
“…Visual scanning training alone was shown to improve significantly neglect in one level Ib study (Weinberg et al, 1977). Spatiomotor or visuo-spatiomotor cueing improved neglect significantly in one level Ib (Kalra et al, 1997) and two level IIa studies (Lin et al, 1996;Frassinetti et al, 2001). Visual cueing with kinetic stimuli was found to bring significant, albeit transient, improvement in three level IIa studies (Butter et al, 1990;Pizzamiglio et al, 1990;Butter and Kirsch, 1995).…”
Section: Rehabilitation Of Ulnmentioning
confidence: 93%
“…Measures of functional ability / disability as a primary outcome measure were used. Twenty‐three trials were identified as meeting the inclusion criteria, eleven of which were new to this update (Cherney, Halper, & Papachronis, 2002; Cottam, 1987; Edmans, Webster, & Lincoln, 2000; Fanthome, Lincoln, Drummond, & Walker, 1995; Ferreira, Leite Lopes, Luiz, Cardoso, & AndrĂ©, 2011; Fong et al., 2007; Kalra, Perez, Gupta, & Wittink, 1997; Kerkhoff et al., 2012; Luukkainen‐Markkula, Tarkka, Pitkanen, Sivenius, & Hamalainen, 2009; Mizuno et al., 2011; Nys, Seurinck, & Dijkerman, 2008; Polanowska, Seniow, Paprot, Leniak, & Czonkowska, 2009; Robertson, 1990; Robertson, McMillan, MacLeod, Edgeworth, & Brock, 2002; Rossi et al., 1990; Rusconi, Meinecke, Sbrissa, & Bernardini, 2002; Schroder, Wist, & Homberg, 2008; Tsang, Sze, & Fong, 2009; Turton, O'Leary, Gabb, Woodward, & Gilchrist, 2010; Weinberg et al., 1977; Welfringer, Leifert‐Fiebach, Babinsky, & Brandt, 2011; Wiart et al., 1997; Zeloni, Farne, & Baccini, 2002). Meta‐analyses showed no significant persistent effect either on standardized assessments or for functional ability.…”
Section: Interventionsmentioning
confidence: 99%
“…Other studies on poststroke cognitive impairment have focused on the prognostic value of isolated impairments such as unilateral neglect, 11,12 anosognosia, 13 aphasia, 14 or apraxia. 15 A detailed neuropsychological evaluation covering the whole cognitive spectrum in acute stroke has not been reported, probably because of uncertainty about the feasibility and reliability of such early testing.…”
Section: Abstract-objectivementioning
confidence: 99%